The Relationship between Peer Social Support with Assertiveness of Adolescent Victims of Bullying - Azzahra, Aurelya; Firman, Firman; Sukma, Dina; Hariko, Rezki (Counseling and Humanities Review, 2025)
Nowadays, bullying among adolescents, especially in the school environment, continues to show an increase, which has a major impact on the mental health of victims. One phenomenon that often appears in adolescent victims of bullying is low assertiveness, which is reflected in the tendency of victims to remain silent, unable to express their opinions, and not daring to defend their personal rights. One of the factors that affect assertiveness is the situation of the peer environment (peer social support). This study aims to describe the level of peer social support and assertiveness in adolescent victims of bullying, and analyze the relationship between the two. This study uses a quantitative method of correlational type. The population was 246 students of SMP Negeri 7 Padang aged 13–15 years (48.3% male and 51.7% female) who were identified as bullying victims. A sample of 152 students was taken by Stratified Random Sampling based on class strata. Data were collected using a peer social support questionnaire and a bullying victim assertiveness questionnaire, with sample items "Friends comfort me when I am belittled by others" and "I keep quiet when friends take my things without permission". The results of data analysis using the Pearson product moment technique, the results showed that peer social support and assertiveness were in the high category. Pearson correlation indicated a moderate positive association between peer social support and assertiveness, r = 0.462, 95% CI (0.40-0.59), 0.000 < 0.001, N = 152. There is a positive and significant relationship between peer social support and assertiveness of adolescent victims of bullying. The higher the peer social support, the higher the assertiveness of students who are victims of bullying.